MAPPING BATHYMETRY BY LANDSAT DATA IN SHALLOW COASTAL ENVIRONMENT (CASE STUDY: THE SOUTHEAST OF THE CASPIAN SEA) - L. Amini; A. A. Kakroodi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Compared to traditional methods, remote sensing (RS) technique is an efficient, fast, low-priced and effective solution in bathymetry. In this study, a linear equation was applied between field and reflectance data to achieve bathymetry map. Landsat-8 is characterized by additional visible band compared with previous Landsat bands on coastal zone application, therefore, we apply two regions of spectrum to compare the accuracy of bathymetry, Bands 1, 3, 4 and bands 2, 3 and 4 respectively. Furthermore, Logarithmic transformation also applied on both spectral regions to have bathymetry map. The coefficient obtained from reflectance and filed data was applied on Tm bands to retrieve the bathymetry of Gomishan lagoon in 2000. The results show that the second spectral region, Bands 2, 3 and 4, is highly correlated with filed data and more accurate (R2 = 0.94, RMSE = 0.35). Moreover, there is a relatively high accuracy between the retrieval of Gomishan bathymetry and the report of recent studies.